Speciation Associated with Shifts in Migratory Behavior in an Avian Radiation - Gómez Bahamón, Valentina (2020)
Gómez-Bahamón et al. show that speciation is associated with changes in migratory behavior in fork-tailed flycatchers (Tyrannus savana). Divergence occurred through loss of migratory behavior of a single lineage. This mode of speciation likely occurred across New World flycatchers (Tyrannidae).